2004
DOI: 10.1016/j.cognition.2003.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of memory circuits to language: the declarative/procedural model

Abstract: The structure of the brain and the nature of evolution suggest that, despite its uniqueness, language likely depends on brain systems that also subserve other functions. The declarative/procedural (DP) model claims that the mental lexicon of memorized word-specific knowledge depends on the largely temporal-lobe substrates of declarative memory, which underlies the storage and use of knowledge of facts and events. The mental grammar, which subserves the rule-governed combination of lexical items into complex re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

115
1,387
8
71

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,494 publications
(1,581 citation statements)
references
References 262 publications
(362 reference statements)
115
1,387
8
71
Order By: Relevance
“…Ullman described that language learning involves both procedural (or implicit) memory involving frontal/basal ganglia circuits, particularly the nigro‐striatal system, and declarative (or explicit) memory mainly relying on hippocampal structures [Ullman, 2004]. Based on findings of a Go‐NoGo study including patients with basal ganglia disorders, it has been suggested that the N2 is associated with the nigo‐striatal system for pre‐motor inhibition, whereas the P3 is more associated with the mesocortico‐limbic system involved in outcome monitoring [Beste, Willemssen, Saft, & Falkenstein, 2010].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ullman described that language learning involves both procedural (or implicit) memory involving frontal/basal ganglia circuits, particularly the nigro‐striatal system, and declarative (or explicit) memory mainly relying on hippocampal structures [Ullman, 2004]. Based on findings of a Go‐NoGo study including patients with basal ganglia disorders, it has been suggested that the N2 is associated with the nigo‐striatal system for pre‐motor inhibition, whereas the P3 is more associated with the mesocortico‐limbic system involved in outcome monitoring [Beste, Willemssen, Saft, & Falkenstein, 2010].…”
Section: Discussionmentioning
confidence: 99%
“…Explicit learning relies mainly on the Medial Temporal Lobe, including the hippocampus, with connections to other brain areas such as the prefrontal cortex [e.g., Reber, 2013]. However, it has been found that in some situations the hippocampus is also involved in implicit learning [e.g., Hannula & Greene, 2012; Poldrack & Rodriguez, 2003], and that the neural networks of implicit and explicit learning interact [Destrebecqz et al, 2005; Ullman, 2004]. Thus, the different neural networks involved in implicit and explicit learning can overlap and interact depending on the learning task.…”
Section: Introductionmentioning
confidence: 99%
“…aaf gum *aaf trul pel rüfi). The reader is referred to previous studies (Opitz & Friederici, 2003;2004) employing this artificial language for further examples and a schematic presentation of the underlying grammar system.…”
Section: Methodsmentioning
confidence: 99%
“…Consistent with previous findings, however, PNFA patients were not sensitive to either class of syntactic error (morphosyntactic or word class substitution errors). One possible explanation is that the rule governing regular verb morphological processing (adding "-ed" to the citation form of the verb) is degraded or cannot be processed in these patients (Ullman, 2004;Ullman et al, 1997), although other data conflicts with this interpretation (Ash, Koenig, Moore, & Grossman, submitted;Bird, Lambon Ralph, Seidenberg, McClelland, & Patterson, 2003;Patterson, Lambon Ralph, Hodges, & McClelland, 2001). …”
Section: Sentence Processing In Pnfamentioning
confidence: 98%